Study on Void Reactivity of Liquid Metal Fast Breeder Reactor - Azizul Khakim; T. Yokoyama; Hisashi Ninokata (Institut Teknologi Bandung, 2008)
Liquid Metal Fast Breeder Reactor (LMFBR) usually has positive void reactivity which is not favorable to the reactor safety. Therefore, the void generation should be avoided during normal reactor operation. Design of reactor core should consider the parameters that influence the void reactivity in order to minimize it, should void be generated during an accident. In this study, several parameters have been evaluated to observe their contribution to the overall void reactivity, such as the build-up of minor actinides (MAs), different inner and outer core height, heterogeneous core configuration, upper plenum, upper axial blanket, voiding in the inner and outer core and the effect of P/D. The study is performed in 3-D heterogeneous geometry using Monte Carlo Method of MVP Code with JENDL-3.3